Pengaturan panas tubuh (sistem termoregulasi) pada hewan vertebrata - Nisa, Rany Hilyatan; Rahma, Suhaila; Agata, Nadhila Ari; Sholihah, Mahira Ahnaf; Salsabila, Salwa (Maliki Interdisciplinary Journal, 2024)
Thermoregulation is a process of regulating body physiology in the form of body heat to keep the body in a state of homeostasis. This process is necessary for the body to remain in a state of homeostasis or the body's biological system to balance the state of the body with the external environment. The process of thermoregulation involves the body's biochemical mechanisms that are regulated in the hypothalamus through the hormonal system. The method used in this study is direct observation of experimental animals using three treatment variables, namely treatment using hot water, treatment using cold water and treatment using water with room temperature. The results of this observation show extreme differences in body temperature that occur in thermoconformer animals (cold-blooded) while in thermoregulator animals (warm-blooded) the difference in body temperature shown is small so that the heat generated by the body remains stable.